DESPITE THE FACT THAT THERE IS CURRENTLY CLEAR HYPERTENSION TREATMENT STRATEGY, WHY DOES BP CONTROL RATES REMAIN POOR WORLDWIDE? - Bositkhonov Akmalkhon Nosirkhon ugli; Ruzmetova Shakhnoza Davronbekovna (Web of Journals Publishing, 2023)
Despite the fact that the causes of hypertension have been studied at the molecular level and precise treatment strategies have been developed, the level of blood pressure control remains low worldwide. What could be the reason? This article is about that.
Keywords: Hypertension,blood pressure, Poor adherence, White-coat phenomenon, Marked brachial artery calcification, Clinician inertia, Lifestyle factors.